(untitled) (Jurnal Bahasa, 2003)
Language has always held a distinctive status in the world of literature. It has long been regarded as a tool in the literature world. Through language, an author creatively generates a narration or storyline. Postmodern thories have utilised language as a discourse as manifested in the analysis of structuralism, semiotic and post-structuralism. The discussion in the world of literature is actually a discussion on language and its discourse. In fact, a theory called stylistic was born solely to analyse literature from the viewpoint of language. This article attempts to discuss all the discourses so that we will be able to see the roles and evaluation of language in the world of literature theory.